The Influence Of Tool Geometry Towards Cutting Performance On Aluminium 7075 - Jumali, Muhammad Syafik (UTeM, 2016)
Aerospace industries often use machining while manufacturing aerospace parts. Machining is done using general endmills that have helix angle of 30o. These endmills give mixed machining results of surface roughness and tool wear depending on the tool manufacturer. This research aims to produce endmill with optimum geometry in terms of the helix angle, primary radial relief angle and secondary relief angle. The endmill is tested on Aluminium 7075 and data on surface roughness and tool wear is collected. Endmill with 10 mm diameter of Tungsten Carbide material is used in this research. Helix angle is varied between 30o-60o, primary radial relief angle varied between 5o-9o while secondary relief angle varied between 14o-17o. Helix angle, primary relief angle and secondary relief angle are the variable parameters. Design of Experiment (DOE) using Full Factorial method is used to generate the matrix of endmill design. 8 samples are prepared with 1 replication means 16 end mills are produced in total. An L-shaped part is machined where the surface roughness is measured both radial and axial by using cutting speed of 600 m/min. Tool wear is examined by studying flank wear. The desirable endmill will have a combination of minimal surface roughness and tool wear. The results of this research show that higher helix angle gives higher tool wear, higher axial surface roughness and higher radial surface roughness and vice versa. Higher primary radial relief angle gives higher tool wear, lower radial surface roughness and higher axial surface roughness and vice versa. Higher secondary radial relief angle gives lower tool wear, higher radial surface roughness and lower axial surface roughness and vice versa. The optimum endmill parameter for helix angle, primary relief angle and secondary relief angle is 30o, 9o and 14o respectively. This research will be very valuable for industries involved with machining Aluminium 7075 namely aerospace industries as it will provide the optimum endmill angles in order to machine Aluminium 7075.